2014
DOI: 10.1007/s10903-013-9961-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Access to Sexual Health Services Among Teens in Toronto: Does Immigration Matter?

Abstract: This manuscript explores predictors of access to sexual health services among urban immigrant adolescents who live in Toronto, Canada. Surveys (n = 1216) were collected from pre-existing youth groups in community settings. A binary logistic multivariate model was developed to examine associations between access to sexual health services and a series of individual, interpersonal, and structural variables. Sexual activity, age, race, and social resources each had significant partial impact on access to sexual he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Our study found that Muslim immigrant women like other immigrant groups in Canada face several challenges during their settlement like difficulty findings jobs despite being highly educated and skilled, experiencing decline in social class, having limited social support, language difficulties, and lack/limited knowledge about the Canadian health care system and resources [10][11][12][13][14][15][16][17][18][19][20][36][37][38]. However, Muslim women wearing the hijab faced additional challenges of tangible discrimination and abuse in employment and public spaces.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our study found that Muslim immigrant women like other immigrant groups in Canada face several challenges during their settlement like difficulty findings jobs despite being highly educated and skilled, experiencing decline in social class, having limited social support, language difficulties, and lack/limited knowledge about the Canadian health care system and resources [10][11][12][13][14][15][16][17][18][19][20][36][37][38]. However, Muslim women wearing the hijab faced additional challenges of tangible discrimination and abuse in employment and public spaces.…”
Section: Discussionmentioning
confidence: 79%
“…Other Ontario studies that have examined rates of cancer screening by region of origin showed that immigrant women from regions with high Muslim populations (i.e., South Asia, the Middle East and North Africa) had lower rates of cervical and breast cancer screening than their immigrant counterparts [10][11][12]. Canadian Muslims experience difficulties accessing sexual health information and cancer screening services due to systemic barriers (e.g., lack of a family physician, inconvenient clinic hours, language difficulties), dominant discourses that discourage open dialogue about sexualities within their communities, religious pedagogy and strict regulations regarding modesty, premarital virginity and sexual behaviour [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they elaborated on how this approach will save them time and money as they did not have to take time off from work or pay for commuting. These are some of the barriers that have been identified in the literature [13, 16, 1820, 44] and HPV self-sampling has the potential to overcome. Our findings supported earlier studies that explored attitudes of women towards HPV self-sampling [2227].…”
Section: Discussionmentioning
confidence: 99%
“…In Canada visible minority and immigrant groups still face personal and systemic barriers to accessing and using related health information and resources, despite the provision of ethno-specific services -a significant progress over the previous colour-blind approaches to HIV and AIDS (Catungal 2013). These barriers include language, poor communication, lack of transport, HIV stigma, fear of encountering racism, distrust of health systems, and an uneven geographic distribution of services, which are often located far from the neighbourhoods with concentrated economic disadvantage and high levels of immigration (Kaukinen and Fulcher 2006;Kteily-Hawa 2013;Salehi, Hynie, and Flicker 2014;Vlassoff and Ali 2011;Worthington et al 2013).…”
Section: Introductionmentioning
confidence: 99%